Effectiveness of Problem-Based Learning with The Help of Microsoft Teams to Improve Students Learning Outcomes - Mutammam, Muhamad Badrul; Wulandari, Evi Novita (Media Pendidikan Matematika, 2025)
One of the learning models that can implement hybrid learning by the objectives of the curriculum in Indonesia is problem-based learning. Hybrid learning can run well with the help of technology. One of the platforms that can be used in learning is Microsoft Teams. This study aims to examine the effectiveness of problem-based learning with the help of Microsoft Teams. This study used experimental research methods with the research population, namely the set of VII classes at SMP Negeri 53 Surabaya. While the research sample is a set of students from a class taken randomly because the classes in the population are relatively homogeneous. Problem-based learning (PBL) assisted by Microsoft Teams effectively improves learning outcomes. This is indicated by an increase in learning outcomes of at least 70 points, the teacher's ability to manage learning gets a score of at least 3 for each assessment aspect, student activities by the ideal time, and students' positive response to learning at least 81.08% for each assessment aspect.